Primary primitive neuroectodermal tumor of the cervix confirmed with molecular analysis in a pregnant woman: A case report and literature review - Wei, Ding; Jianguo, Zhao; Xiao, Li; Pengpeng, Qu (Frontiers in Genetics, 2022)
Primary primitive neuroectodermal tumor (PNET) in the female tract is rare. Recently, a case of cervical PNET was diagnosed in our hospital. A 29-year-old pregnant woman presented with a cystic-solid cervical mass at the 7th week of gestation. The mass grew rapidly during follow-up and ruptured at the 22nd week. A biopsy was performed on the mass. Pathological examination revealed a malignant neoplasm composed of small cells which exhibited positive immunohistochemical (IHC) staining for CD99, SYN and FLI1. Fluorescence in situ hybridization (FISH) displayed the presence of EWS-FLI1 fusion gene resulting from the chromosomal translocation t (11;22, q24;q12), which confirmed the diagnosis of cervical PNET. The reverse transcription-polymerase chain reaction (RT-PCR) results showed type 2 EWS-FLI1 fusion occurred in this tumor, suggesting a poor prognosis. The patient underwent surgical resection and was given adjuvant chemotherapy followed by pelvic radiotherapy. PNET arising from the genital tract, especially in the uterine cervix, is very rare and presents a diagnostic challenge. FISH and RT-PCR analysis are helpful for the diagnosis of such a tumor at an unusual site as in the present case.